Políticas de educação de jovens e adultos no Brasil: Uberlândia - MG (anos 80 e 90) - Vieira, Maria Clarisse (2000)
The theme of this dissertation is about the policy of education of the young and adults in the capitalist Brazilian context, focusing the experience which Uberlândia, in the Estate of Minas Gerais, has been through, during 1980 and 1990. This research has been accomplished by surveying statistical data, institutional documents, questionnaires and oral interviews with students, teachers, directors and municipal Secretary of Education. The research has been organised as follows: at first, it has been analysed the social and economical context of the end of the XX century, in which the policy of the young and adult teaching has been developed. Directly afterwards there is a historical research on the young and adults educational policy, especially that which was developed during the 90s. In the municipal scope it has bee analysed the historical course of the municipal programmes of education of the young and adults, during the 80s and 90s, registering its experience and proposition and its inter- relation with national public policy. The research points out the education of the young and adults as a social right, constituent of the modern citizenship, thus indicating the importance of the induction of the government in the development of this educational field in Brazil.